Features of the Introduction of Helicobacter Pylori Infection in Children - N. H. Khudayberganova; I. T. Aliqulov; N. M. Narziyev; B. I. Abdakimova; B. M. Solixov (Scientific Trends, 2024)
The article outlines modern views on the principles of therapy for Helicobacter pylori infection, the resistance of the pathogen, the drugs used, their combinations and effectiveness in achieving remission and reducing the frequency of relapses.
Keywords: Helicobacter pylori infection, treatment, effectiveness.